Surfactant modified zeolite Y as a sorbent for some chromium and arsenic species in water - Nik Malek, Nik Ahmad Nizam (2007)
The removal of some chromium and arsenic species from water by the surfactant-modified zeolite Y (SMZY) and unmodified zeolite Y was studied. Zeolite NaY was successfully synthesized from rice husk ash via seeding method involving the preparation of two separate gel formations. The synthesized and commercial zeolite NaY were characterized with XRD, FTIR, surface area and elemental analysis. The total cation exchange capacity (CEC) and external cation exchange capacity (ECEC) for the synthesis was higher than the commercial one due to the lower ratio of silica to alumina for the synthesized than the commercial zeolite Y. The zeolite NaY was subsequently modified with hexadecyltrimethyl ammonium (HDTMA) at the amount equal of 50%, 100% and 200% of ECEC of the zeolite. The study of Cr(III) removal showed the synthesized zeolite NaY effectively removed Cr(III) than the commercial one. The equilibrium sorption data fitted the Langmuir and Freundlich isotherm models and the kinetic study was followed the pseudo second order model. The slight decrease of the Cr(III) removal capacity for SMZY indicated that the sorbed cationic surfactant blocked sorption sites for Cr(III). While the unmodified zeolite had little affinity for the Cr(VI) and As(V) species, the SMZY showed significant removal of both species. The adsorption equilibrium data are best fitted to the Langmuir model. The removal of Cr(VI) was highest when the synthesized zeolite NaY was modified such that HDTMA achieved 100% of its ECEC. The SMZY-synthesis showed an adsorption of As(V) capacity higher than the SMZY-commercial. Because the As(III) exists form as neutral species in water, the removal of As(III) from water between unmodified and SMZY showed only a slight difference. The effects of different surfaces coverage of HDTMA-zeolite on the sorption of these species were insignificant. The SMZY was proven to be useful in removing cationic and anionic forms of arsenic and chromium in water simultaneously compared to the unmodified zeolite Y since it has the affinity for both cations and anions.